John Stuart Mill, utility and the family: attacking ‘the citadel of the enemy’ - McCabe, Helen (Assoc. R.I.P, 2015)
John Stuart Mill’s commitment to female equality has generally been acknowledged as positive, but certain passages have been damned as anti-feminist or myopic regarding the reality of patriarchy, and used as sticks with which to beat both Mill’s theory and liberal feminism in general. Yet Mill may not be guilty of all the oversights, misunderstandings, self-contradictions, conservatisms or misogyny of which he has been accused. He was genuinely committed to making women fully equal citizens in a much more equal, diverse, free and harmonious future society, but, as in all things, Mill’s feminism is nuanced and multi-faceted – he wanted to attack the family as the ‘citadel’ of male dominance, and yet acknowledged (as many liberal philosophers do not) that citizens are made in the home; that whatever else happens, domestic labour must be done; that there would be economic as well as moral outcomes of flooding the labour market with those currently banished from it; that intimate relationships are fundamentally important to utility; and that the act of conception entailed social responsibilities. This paper looks beyond what Mill says in The Subjection of Women, and particularly at what he says about justice in co-operative associations in Principles of Political Economy, in order to present a revisionist account of Mill’s feminism and, specifically, his attitude to the family.